Funding biodiversity protection in central and eastern Europe – a case study of Bosnia Herzegovina. - Dautbasic, Mirza; Ioras, Florin; Abrudan, Ioan Vasile; Ratnasingam, Jega (University of Agricultural Sciences and Veterinary Medicine, Cluj-Napoca, 2010)
Biodiversity conservation has drawn considerable attention as to where the funding is available in order for governments concerned with the conservation of biodiversity to fulfil their obligations. This paper examines if financing resources provided through Global Environmental Facility (GEF) in Bosnia Herzegovina could be supplemented with locally voluntary provided funding to lead to an appropriate protection level of threatened species. A study was conducted on a 1189 persons sample to establish the local population willingness to contribute to GEF sponsored biodiversity conservation projects. It was found that the local people are willing to contribute positively higher than the actual spending of the GEF and findings can be used to argue for more attention to preferences of the public in decision making on biodiversity protection activity and spending in Bosnia Herzegovina.